To evaluate the role of positron emission tomography-computerized tomography in initial staging of carcinoma breast - Anju Kansal; Gaurav Jaswal; Shreya Garg; Manraj Singh Kang; Hanuman Prasad Yadav; Raja Paramjeet Singh Banipal; Pardeep Garg; Taranjeet Kaur (Wolters Kluwer Medknow Publications, 2021)
Background: Breast cancer is the most common cancer in urban and second common in rural Indian women. In India, in spite of the best treatment available being given to the patients they lose their lives because of paucity of diagnostic aids and lack of an organized breast cancer screening program. Early detection, accurate staging, and initiation of appropriate therapy are the key factors for improving the treatment outcome and prognosis of the disease for the patients. Traditional staging methods include clinical examination, blood tests, chest X-ray, ultrasound of the abdomen, and/or skeletal survey. As these tests lack sensitivity and specificity, these are being scaled down. The hybrid positron emission tomography-computerized tomography (PET-CT) is a unique tool in the field of imaging modalities that combines the effectiveness of PET and CT. This study was undertaken to assess the efficacy and accuracy of PET-CT as a single-session staging modality in the very initial stage itself and if it can replace the conventional means of staging. Methods: This was a cross-sectional study conducted in the Radiotherapy department at GGS Medical College and Hospital Faridkot from March 2014 to October 2015. 52 patients with newly diagnosed and histopathologically proven carcinoma breast were staged by conventional modalities (clinical examination, blood tests, X-ray chest, mammography, ultrasonography abdomen, skeletal survey) and by 18F-fluorodeoxyglucose (18F FDG) PET/CT. PET-CT images were used for the detection, localization, staging of tumors and detection, evaluation, and diagnosis of metastatic lesions, disease burden and organ function along with treatment planning and planning therapeutic procedures. Following the completion of initial study, the results of 18F FDG PET-CT staging in comparison with conventional staging method were assessed. Along with this, the accuracy, changes in staging of cases of carcinoma breast and cost-effectiveness of 18F-FDG PET-CT were also studied. Results: All the pathologic entities identified by conventional imaging were also perceived with 18F-FDG PET/CT. Therefore, we recommend the use of PET/CT as an important imaging modality for initial diagnosis of carcinoma breast.